PDCT-08. SUPERIOR OUTCOME FOR BRAF V600E PEDIATRIC GLIOMAS TREATED WITH TARGETED BRAF INHIBITION. (11th November 2019) - Nobre, Liana; Zapotocky, Michal; Ramaswamy, Vijay; Ryall, Scott; Bennett, Julie; Balaguer Guill, Julia; Baroni, Lorena; Bartels, Ute; Bornhorst, Miriam; Boue`, Daniel; Chintagumpala, Murali; Cruz, Ofelia; et al.
Abstract: BACKGROUND: Children with pediatric low grade glioma's (PLGG) harboring BRAF V600E mutation have poor outcome due to relative resistance to chemo-radiation and higher risk of malignant transformation. However, the role of targeted BRAF inhibition in these tumors is poorly defined. METHODS: We assembled an international cohort of children with BRAF V600E mutant gliomas treated with BRAF inhibition, from 29 centers participating in the PLGG taskforce, and collected response, survival and molecular parameters. RESULTS: Sixty-seven patients were treated with BRAFi (56 PLGG and 11 high grade gliomas) for a median time of 17.4 months (6 – 61 months), with 13 PLGG treated upfront. Objective responses was observed in 80% of PLGG patients compared to 28% with conventional chemotherapy (p< 0.001). Rapid responses were observed in most PLGG patients (median of 4 months), sustained in 86% of tumors up to 5 years while on therapy. In contrast, only 36% of PHGG responded to BRAFi with all but one tumor progressing within 18 months. Seventeen patients with PLGG discontinued BRAFi and 76.5% (13/17) progressed rapidly after discontinuation (median time 2.3 months). However, upon re-challenge with BRAFi therapy, 90% achieved an objective response. Poor prognostic factors to conventional therapies such as concomitant homozygous deletion of CDKN2A or H3K27M mutation were not associated with lack of response to BRAFi. Overall these responses translated to 2-year progression-free survival of 0.636 (95%CI 0.505–0.802) and 0.43 (95% CI 0.32–0.57) for BRAFi and chemotherapy treated BRAF V600E PLGG respectively (p=0.003). CONCLUSION: The use of BRAFi results in objective, robust and durable responses in BRAF V600E PLGG and is associated with favorable survival. Larger prospective studies will be required to determine appropriate regiments, and long-term functional outcomes with BRAFi therapy in childhood gliomas.